The Works of John Ruskin, Volume 20, Lectures on Art - Ruskin, John 1819-1900 (Cambridge library collection. Works of John Ruskin, 1905)
The influence of John Ruskin (1819–1900), both on his own time and on artistic and social developments in the twentieth century, cannot be over-stated. He changed Victorian perceptions of art, and was the main influence behind 'Gothic revival' architecture. As a social critic, he argued for the improvement of the condition of the poor, and against the increasing mechanisation of work in factories, which he believed was dull and soul-destroying. The thirty-nine volumes of the Library Edition of his works, published between 1903 and 1912, are themselves a remarkable achievement, in which his books and essays - almost all highly illustrated - are given a biographical and critical context in extended introductory essays and in the 'Minor Ruskiniana' - extracts from letters, articles and reminiscences both by and about Ruskin. This twentieth volume contains 'Lectures on Art' and 'Aratra Pentelici'